Simulation and Comparative Analysis of DSDV and DSR Routing Protocols in Manets - Kumar, Adarsh (My University, 2007)
With current advances in technology, wireless networks are increasing in popularity. Wireless networks allow users the freedom to travel from one location to another without interruption of their computing services. However, wireless networks require the existence of a wired base station (BS) in order for the wireless user to send/receive messages. Ad hoc networks, a subset of wireless networks, allow the formation of a wireless network without the need for a BS. All participating users in an ad hoc network agree to accept and forward messages, to and from each other. With this flexibility, wireless networks have the ability to form anywhere, at any time, as long as two or more wireless users are willing to communicate. In an ad hoc network, the ability to send a message to a group of users, based solely on their geographic location, is desirable. Rescue missions, military scenarios, and even advertising schemes benefit from this type of message delivery service. However, before implementation occurs, an ad hoc network protocol such as a geocast protocol must be tested under realistic conditions including, but not limited to, a sensible transmission range, limited buffer for storage of messages, and realistic movements of the wireless users (i.e., a mobility model). The results presented in this thesis focus on two routing protocols in an attempt to compare the effects that different routing protocols have on an ad hoc network protocol. It is obvious that wireless users will travel from one location to another. However, representing their exact movements is not so simple. The results presented in this thesis illustrate the importance in carefully evaluating and implementing routing protocols when evaluating an ad hoc network protocol.
Keywords: Wireless Networks; Network Protocol; Computer Science